2020
DOI: 10.1101/gr.260141.119
|View full text |Cite
|
Sign up to set email alerts
|

Human auditory ossicles as an alternative optimal source of ancient DNA

Abstract: DNA recovery from ancient human remains has revolutionized our ability to reconstruct the genetic landscape of the past. Ancient DNA research has benefited from the identification of skeletal elements, such as the cochlear part of the osseous inner ear, that provides optimal contexts for DNA preservation; however, the rich genetic information obtained from the

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
22
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
6
2
1

Relationship

2
7

Authors

Journals

citations
Cited by 46 publications
(23 citation statements)
references
References 71 publications
1
22
0
Order By: Relevance
“…We generated powder from the skeletal remains of all individuals excavated from sites throughout the Caribbean (see Supplementary Information section 2 for archaeological site information and Figures S1 - S11 for maps showing the location of the islands and/or sites studied). Powder was produced from a cochlea 38 , 39 , tooth, phalanx, or ossicle 40 from each individual in a clean room facility at Harvard Medical School (Boston, USA), University College Dublin (Dublin, Ireland), or the University of Vienna (Vienna, Austria); see Supplementary Data 2 for the skeletal element used for each individual and location of powder preparation.…”
Section: Methodsmentioning
confidence: 99%
“…We generated powder from the skeletal remains of all individuals excavated from sites throughout the Caribbean (see Supplementary Information section 2 for archaeological site information and Figures S1 - S11 for maps showing the location of the islands and/or sites studied). Powder was produced from a cochlea 38 , 39 , tooth, phalanx, or ossicle 40 from each individual in a clean room facility at Harvard Medical School (Boston, USA), University College Dublin (Dublin, Ireland), or the University of Vienna (Vienna, Austria); see Supplementary Data 2 for the skeletal element used for each individual and location of powder preparation.…”
Section: Methodsmentioning
confidence: 99%
“…It has often been assumed that this better preservation is somehow related to the unusually high density of the petrous bone [ 8 ]. Other hypotheses for better DNA preservation are the presence of a large number of mineralized osteocytes may facilitate the preservation of DNA in fossil bones [ 15 ], that the petrous bone is essentially not remodeled [ 16 ], or bones that are most likely to preserve DNA are those with the highest amounts of endogenous DNA in vivo, namely bones with the highest concentrations of osteocytes [ 17 ].…”
Section: Introductionmentioning
confidence: 99%
“…Bulk staining shows that lacunae and canaliculi seal off the apoptotic DNA contents which may be another explanation for better preservation of DNA [ 28 ]. Here we address the hypothesis that one possible reason that DNA is relatively well preserved in fossil petrous bone is because the fresh petrous bone contains significantly more DNA than other bones [ 15 ]. Andranowski measured DNA yields from different bone tissues (excluding the petrous bone) and assumed a correlation between the number of osteocyte lacuna numbers and DNA yields.…”
Section: Introductionmentioning
confidence: 99%
“…Among the methodological innovations that have made possible to overcome these difficulties there is the identification of the best skeletal elements, of which in primis petrous bones ( Edson et al, 2009 ; Gamba et al, 2014 ; Pinhasi et al, 2015 ). Even though, this skeletal element can lead to endogenous DNA yields that are up to 50–100-fold higher than those obtained from other bones, recent studies demonstrated that other samples ( in situ molars, thoracic vertebrae, talus, and distal phalanx) can yield adequate DNA for most applications in human palaeogenetics ( Higgins et al, 2013 ; Hansen et al, 2017 ; Parker et al, 2020 ), especially ear ossicles ( Sirak et al, 2020 ). Important methodological improvements also regarded the development of increasingly efficient extraction protocols and genotyping kits.…”
Section: Discussionmentioning
confidence: 99%